Negotiating The Social Body: The Autonomy and Subjectivity of Javanese Female Singer “Sinden” in Eka Uget-Uget - Vici Duta Febriansyah; Sri Kusumo Habsari; Eva Farhah (Universitas Sebelas Maret, 2022)
Sinden originated from the word